PERNIKAHAN SAKINAH MAWADDAH WARAHMAH BAGI PENYANDANG TUNANETRA (STUDI KASUS KAMPUNG TUNANETRA KECAMATAN ILIR TIMUR 2 PALEMBANG) - Silfa Afriyani; Arne Huzaimah; Napisah Napisah (Usroh: Jurnal Hukum Keluarga Islam, 2021)
A marriage aims to create a sakinah, mawaddah, warahmah household life. From this goal it becomes a desire for every married couple, as well as for blind couples. So this research the authors formulate the problems, namely: (1) how to understand the family sakinah, mawaddah, warahmah for blind couples (2) how are the efforts to form a sakinah, mawaddah, warahmah household for blind couples. This research method uses field research methods (field research), the data sources used are primary data sources obtained from interviews with respondents in the field, then secondary data obtained from books and scientific papers. Data collection techniques are direct interviews, field survey and documentation. The data analysis used was qualitative inductive, namely drawing conclusions from general statements drawn to specific statements. From the results of the research that has been done, it can be concluded that: (1) Understanding the sakinah, mawaddah, warahmah family for blind couples is a family that is peaceful, peaceful, gives love to all family members, is always grateful to Allah SWT, can solve problems by well and of course support each other. (2) As for how to form a sakinah, mawaddah, warahmah family, namely by promoting a sense of love and affection between family members, understanding each other, understanding, appreciating, not demanding more of each other, establishing good communication, and always solving problems by giving in to each other. so that things that are not desirable happen. Key words: Visually impaired, family, sakinah mawaddah warahmah